Modern tanks and AFVs 1991-present armoured fighting vehicles - Hart, Russell; Hart, Stephen (Technical guides, 2019)
From the Gulf Wars to Afghanistan, Chechnya to the Crimea and Ukraine, Yemen to the Syrian Civil War, modern warfare has made strategic use of tanks and AVFS. Here's all every military enthusiast needs to know about those main battle tanks, armored personnel carriers, infantry fighting vehicles, self-propelled guns, and other vehicles. The examples discussed include the Chinese Type 99 main battle tank, the Korean K-2 Black Panther, the French VBCI infantry fighting vehicle, the Fennek reconnaissance vehicle, and the Russian T-14 Armata. Each profile includes authentic markings and color schemes, and every individual model features detailed specifications.